The degree of consistency of applying parental dietary and sedentary behavior rules as indicators for overweight in children: a cross-sectional study - Emilie L. M. Ruiter; Gerdine A. J. Fransen; Marloes Kleinjan; Koos van der Velden; Gerard R. M. Molleman; Rutger C. M. E. Engels (BMC, 2022)
Abstract Background Review studies increasingly emphasize the importance of the role of parenting in interventions for preventing overweight in children. The aim of this study was to examine typologies regarding how consistently parents apply energy-balance related behavior rules, and the association between these typologies and socio-demographic characteristics, energy balance-related behaviors among school age children, and the prevalence of being overweight. Methods For this cross-sectional study, we had access to a database managed by a Municipal Health Service Department in the Netherlands. In total, 4,865 parents with children 4-12 years of age participated in this survey and completed a standardized questionnaire. Parents classified their consistency of applying rules as "strict", "indulgent", or "no rules". Typologies were identified using latent class analyses. We used regression analyses to examine how the typologies differed with respect to the covariates socio-demographic characteristics, children's energy balance-related behaviors, and weight status. Results We identified four stable, distinct parental typologies with respect to applying dietary and sedentary behavior rules. Overall, we found that parents who apply "overall strict EBRB rules" had the highest level of education and that their children practiced healthier behaviors compared to the children of parents in the other three classes. In addition, we found that parents who apply "indulgent dietary rules and no sedentary rules" had the lowest level of education and the highest percentage of non-Caucasians; in addition, their children 8-12 years of age had the highest likelihood of being overweight compared to children of parents with "no dietary rules". Conclusions Parents' consistency in applying rules regarding dietary and sedentary behaviors was associated with parents' level of education and ethnic background, as well as with children's dietary and sedentary behaviors and their likelihood of becoming overweight. Our results may contribute to helping make healthcare professionals aware that children of parents who do not apply sedentary behavior rules are more likely to become overweight, as well as the importance of encouraging parents to apply strict dietary and sedentary behavior rules. These results can serve as a starting point for developing effective strategies to prevent overweight among children.